(untitled) (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: The objective of this study was to evaluate the cytotoxic, apoptotic, and cell cycle effect of four fractions obtained from the whole aerial part of Solanum nigrum, against three cancer cell lines (MCF-7, A2780, and HT29) and one normal cell line (MRC-5). Materials and Methods: MTT assay was used to assess the cytotoxicity of the four fractions. Then, the most active fraction (ethyl acetate) was further examined by annexin V propidium iodide (PI)/FITC apoptosis assay, cell cycle analysis in MCF7 cells followed by gas chromatographymass spectrometry (GC-MS) analysis. Results: The highest growth inhibition activity was obtained by the ethyl acetate fraction (IC50 10–12 µg/ml) against the three cell lines and that fraction spared the normal cell line MRC5 with IC50 of 31.78 µg/ml. Annexin V PI/FITC revealed a dose-dependent induction of apoptosis in MCF7 cells when treated the ethyl acetate fraction; which also caused a non-dose dependent S phase arrest. The GC-MS analysis of the ethyl acetate fraction showed fatty acids and esters of fatty acids as the significant components. Conclusion: The ethyl acetate fraction from S. nigrum strongly inhibited the growth of breast, ovarian, and colon cancer cell lines, and it was three folds selective against the normal fibroblasts. It also caused the induction of early apoptosis and S phase cell cycle block at 10 µg/mL. Future bioassay-guided fractionation of the ethyl acetate fraction could reveal the active compounds, which can be more investigated in further studies.